A male with type I orofaciodigital syndrome. - Goodship, J (1991)
We describe a three generation family with three females showing minor features of orofaciodigital syndrome type I and a severely affected male in the third generation. In addition to the classical features of OFD I, the male had bilateral duplication of the halluces, a feature diagnostic of OFD II, and an atrioventricular septal defect. Heart defects have not previously been reported in OFD I but have been reported in OFD II. It is important to examine the mothers of all male neonates with orofaciodigital syndrome with care before making a diagnosis of OFD II.